2004
DOI: 10.1038/nn1237
|View full text |Cite
|
Sign up to set email alerts
|

Repelling class discrimination: ephrin-A5 binds to and activates EphB2 receptor signaling

Abstract: The interactions between Eph receptor tyrosine kinases and their ephrin ligands regulate cell migration and axon pathfinding. The EphA receptors are generally thought to become activated by ephrin-A ligands, whereas the EphB receptors interact with ephrin-B ligands. Here we show that two of the most widely studied of these molecules, EphB2 and ephrin-A5, which have never been described to interact with each other, do in fact bind one another with high affinity. Exposure of EphB2-expressing cells to ephrin-A5 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
347
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 410 publications
(365 citation statements)
references
References 38 publications
17
347
1
Order By: Relevance
“…Thus, it is tempting to speculate that EphA4 is the partner of ephrin-A5 in this repulsive/permissive system. In contrast, EphB2, although known to interact with ephrin-A5 16 , does not seem to be a good candidate, as it is equally expressed in both type I and type II SGNs.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, it is tempting to speculate that EphA4 is the partner of ephrin-A5 in this repulsive/permissive system. In contrast, EphB2, although known to interact with ephrin-A5 16 , does not seem to be a good candidate, as it is equally expressed in both type I and type II SGNs.…”
Section: Discussionmentioning
confidence: 92%
“…4). Although it is classically believed that EphA and EphB receptors interact solely with ephrin-A and ephrin-B ligands, respectively, recent work has demonstrated crosstalk between these ephrin subfamilies (Himanen et al, 2004). Future work will be necessary to determine the roles of ephrin-B1 and Eph-A2 in mammary development and to evaluate potential crosstalk between these cell-surface proteins.…”
Section: Ephrin Expressionmentioning
confidence: 99%
“…EphrinA and B differ in their membrane-anchorage and on their receptor affinity: ephrinA are glycosylphosphatidylinositol (GPI)-linked proteins and bind generally to the EphA-receptors, whereas ephrinB have a transmembrane domain and a cytoplasmic region, and interact preferentially with EphB-receptors. Exceptions in the binding discrimination between classes are that ephrinA5, at high concentration, can bind to EphB2 [6], and ephrinB-ligands to EphA4 [7]. Ephrins and their receptors are highly expressed in the developing nervous system and often in complementary gradients inside delimited regions of the central nervous system [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Within the ephrinA group, ephrinA5 has been extensively studied and was shown to be a ligand for EphA3 [11,12], EphA4 [13,14], EphA5 [10], EphA7 [15] and EphB2 [6] receptors. The study of its expression, mainly explored at the mRNA level in the rodent developing brain, has shown that ephrinA5 is present from early organogenesis [16] to postnatal stages throughout the central nervous system.…”
Section: Introductionmentioning
confidence: 99%